(untitled) (Research, Society and Development, 2020)
Chronic migraine (CM) has a wide range of symptoms, with debilitating consequences for those individuals refractory to the conventional treatments. In this context, Transcranial Direct Current Stimulation (tDCS) is a promising technique, although there is still no consensus on the most appropriate protocol, which may vary in relation to the number and interval between the application sessions. The present work consists of a protocol to assess the clinical and cognitive effects of ETCC on CM in the form of a double-blind, randomized and placebo-controlled clinical trial. The sample will consist of women aged between 20 and 45 years with a diagnosis of CM. A sociodemographic questionnaire and instruments for assessing cognitive functions, affective aspects, and clinical evaluation of migraine will be applied. Participants will be randomly distributed among 3 groups: Group 1: will receive a daily tDCS session for 15 minutes; Group 2: will receive two daily tDCS sessions of 15 minutes, with an interval of 20 minutes between them; Group 3: will receive simulated stimulation (sham) for 15 minutes. The anode electrode will be placed on the left dorsolateral prefrontal cortex and the reference electrode on the contralateral supraorbital region. In the Groups 1 and 2 the current will have an intensity of 2mA and will be applied for 10 consecutive days. We expect that tDCS will be effective in reducing symptoms in CM, with a decreased in pain and stress, and an improvement in the cognitive performance. This study will help to define a more appropriate neuromodulation protocol, contributing to the clinical decision making in CM.